Pengaruh Fraud Star terhadap Fraudulent Financial Statement dengan Komite Audit sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Manfaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2016-2020) - Putri Rizkia; Haryono Umar; Indah Kristianti (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2023)
This study examines the fraud star to detect fraudulent financial statements by using the audit committee's financial expertise as a moderating variable. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2011-2014. The purposive sampling method was chosen to determine the 71 companies observed for 5 years so that 355 samples were obtained. The analytical method used is multiple regression analysis with the SPSS version 25 program. The results of the research are able to prove that rationalization and lack of integrity have a negative and significant effect on fraudulent financial statements. Furthermore, the audit committee was not able to moderate the pressure, opportunity, rationalization and capability for fraudulent financial statements, but the audit committee was able to weaken the effect of lack of integrity on fraudulent financial statements. Keywords: Triangle Fraud, Diamond Fraud, Fraud Star, Audit committee, Financial Statement Fraud